2023
DOI: 10.1186/s12912-023-01281-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of BOPPPS combined with TBL in surgical nursing for nursing undergraduates: a mixed-method study

Abstract: Background Surgical Nursing is a core subject for nursing undergraduates that requires active and effective learning strategies to cultivate students’ autonomous learning competencies and critical thinking. The effects of BOPPPS (Bridge-in, Objectives, Pretest, Participatory Learning, Post-test and Summary) model combined with team-based learning (TBL) have rarely been explored in Surgical Nursing courses. Objective To explore the effects of BOPPPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Authors' information 1 The First School of Clinical Medicine, Guangdong Medical University, Dongguan 523808, Guangdong, China; 2 The School of Basic Medicine, Guangdong Medical University, Dongguan 523808, Guangdong, China; 3 Fujian Medical University Union Hospital, Fuzhou 350001, Fujian, China; 4 Department of Public Health and Medical Technology, Xiamen Medical College, Xiamen 361023, Fujian, China; 5 The Graduate School of Guangdong Medical University, Dongguan 523808, Guangdong, China…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors' information 1 The First School of Clinical Medicine, Guangdong Medical University, Dongguan 523808, Guangdong, China; 2 The School of Basic Medicine, Guangdong Medical University, Dongguan 523808, Guangdong, China; 3 Fujian Medical University Union Hospital, Fuzhou 350001, Fujian, China; 4 Department of Public Health and Medical Technology, Xiamen Medical College, Xiamen 361023, Fujian, China; 5 The Graduate School of Guangdong Medical University, Dongguan 523808, Guangdong, China…”
Section: Acknowledgementsmentioning
confidence: 99%
“…BOPPPS teaching method is a novel clinical teaching model, which stimulates students' learning interest through bridge-in (B) introduction, and draws up corresponding training objectives (O) and pre-assessment (P) plans according to the actual situation of students. Various teaching methods are integrated to allow each student to participate in learning (P), and post-assessment (P) is used to evaluate the students' mastery of knowledge and skills and make a summary (S) [1][2]. Situational teaching takes the lead in simulating and designing diagnosis and treatment scenes related to clinical teaching contents and objectives in the teaching process, so as to vividly show the complexity and diversity of clinical diseases in ICU, so as to stimulate and enhance the learning interest and motivation of trainees [3][4].…”
mentioning
confidence: 99%
“…In the past decade, there has been an increasing amount of research on BOPPPS in nursing education, including areas such as medical nursing ( 19 ), surgical nursing ( 20 ), health assessment ( 21 ), and nursing management ( 22 ). These studies indicate that the BOPPS teaching model has a positive impact on student’s academic performance, self-directed learning abilities, and satisfaction with their learning, compared to control groups receiving traditional teaching methods.…”
Section: Introductionmentioning
confidence: 99%
“…The BOPPPS teaching model has been widely applied in medical education. Li et al ( 11 ) found that combining BOPPPS and team-based learning can improve the self-learning and critical thinking abilities of nursing undergraduates. Xu et al ( 12 ) explored the application effect of the mixed BOPPPS teaching model in gynecological clinical internships and demonstrated that the BOPPPS teaching model could stimulate students’ learning interest and initiative, enhance their clinical practice ability, and improve their satisfaction.…”
Section: Introductionmentioning
confidence: 99%